Endometrial expression of steroid receptors in postmenopausal hormone replacement therapy users: relationship to bleeding patterns. Issue 1 (1st January 2008) - Vani, Susheel; Critchley, Hilary O D; Fraser, Ian S; Hickey, Martha
Abstract : Background: Mechanisms of menopausal hormone replacement therapy (HRT)-related bleeding, undoubtedly mediated through endometrial steroid receptors, are poorly understood. We aimed to determine the steroid receptor expression in HRT-exposed endometrium in relation to disturbances of bleeding patterns. Methods: Prospective observational study in a tertiary referral menopause clinic in Western Australia. Thirty-eight outpatient endometrial biopsies (seven from women not on HRT, 31 from HRT users) were collected from 21 postmenopausal women during and outside bleeding episodes. Eleven women provided multiple biopsies. We performed an immunohistochemical analysis of endometrial glandular, stromal, epithelial, perivascular and endothelial expression of progesterone receptor (PR), glucocorticoid receptor (GR), androgen receptor (AR), estrogen receptors α and β (ERα and ERβ) and studied their relationship to bleeding patterns. Results: In HRT users, during a bleeding episode, there was a trend (non-significant) towards a decrease in PR and an increase in GR in endometrial glandular cells. No differences were observed in AR and ER expression. Conclusions: We have been unable to demonstrate significant differences in steroid receptor expression in endometrium of women using HRT who report unscheduled bleeding episodes. These observations differ from the endometrial steroid receptor expression observed with normal menstruation and long-term progestogen-only administration, suggesting that different local mechanisms are involved in HRT-related unscheduled bleeding.